Densely-stacked N-doped mesoporous TiO2/carbon microsphere derived from outdated milk as high-performance electrode material for energy storages. Issue 14 (1st October 2018) - Wang, Yange; Lu, Yang; Luo, Rongjie; Zhang, Yingge; Guo, Yan; Yu, Qiuhong; Liu, Xianming; Kim, Jang-Kyo; Luo, Yongsong
Abstract: Spherical N-doped mesoporous TiO2 /C (MTC) composite micro-particles are produced by spray drying (SD) and carbonization process. The particle size of MTC microsphere is between 2 and 3.4 µm, and the N-doped amorphous C around TiO2 could provide a conductive matrix, and buffer the volume change. When evaluated as electrodes for Li-ion batteries (LIBs) and Li-S batteries (LSBs), the MTC microsphere exhibits relatively high discharge-voltage plateau, excellent capacity retention and rate capability. As anode for LIBs, after 200 cycles, a reversible capacity more than 230 mA h g −1 can achieved at 1 C. And for LSBs, a specific capacity of 1317.7 mA h g −1 at 1 C and the capacity retention of 73.8% after 500 cycles. The superior electrochemical performance is ascribed to robust scaffolding architecture and conductive N-doped carbon matrix. The excellent electrochemical performance and process ability of the MTC microspheres make them very attractive as electrode materials for use in high rate battery application.